1992
DOI: 10.1017/s0141347300017213
|View full text |Cite
|
Sign up to set email alerts
|

Operant Conditioning with Subjects Suffering From Dementia

Abstract: Two experiments are reported in which patients who resided on continuing care psychogeriatric wards were exposed to an operant conditioning procedure. In the first experiment, the subjects were three female patients, all of whom were suffering from severe dementia. For two of the subjects, extended acquisition training was required before evidence of learning was found. Responding under fixed interval (FI) schedules of three different durations was well maintained by the third subject. Evidence of temporal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Although participants without AD exhibited spontaneous recovery of responding during a retention test, participants with AD did not. The performances of the participants with AD, like those reported by Ankus and Quarrington (1972) and Burgess et al (1992) provide further evidence of the possibility of operant learning among older adults with dementia. The use of the NINCDS-ADRDA criteria (McKhann et al, 1984) for inclusion in the present study enables researchers, for the first time, to make statements about the potential for operant conditioning among older adults with probable AD.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Although participants without AD exhibited spontaneous recovery of responding during a retention test, participants with AD did not. The performances of the participants with AD, like those reported by Ankus and Quarrington (1972) and Burgess et al (1992) provide further evidence of the possibility of operant learning among older adults with dementia. The use of the NINCDS-ADRDA criteria (McKhann et al, 1984) for inclusion in the present study enables researchers, for the first time, to make statements about the potential for operant conditioning among older adults with probable AD.…”
Section: Discussionsupporting
confidence: 70%
“…Although a number of basic operant studies have been conducted with cognitively intact older adults (e.g., Baron & Menich, 1985;Baron, Menich, & Perone, 1983;Perone & Baron, 1982;Plaud, Gillund, & Ferraro, 2000), to our knowledge, only two basic studies of the degree to which operant learning can occur in older adults with dementia have been published (Ankus & Quarrington, 1972;Burgess, Wearden, Cox, & Rae, 1992) and we know of none that have appeared since 1992. Although the results of prior investigations suggest that the responding of older adults with dementia may be sensitive to changes in contingencies of reinforcement, researchers in these studies evaluated operant learning in persons with dementia that arose from varied and, at times, poorly characterized causes.…”
Section: West Virginia Universitymentioning
confidence: 99%
“…Both implicit (Burgess, Wearden, Cox, & Rae, 1992;Camp et al, 1993) and explicit (Clare et al, 2000) learning have been demonstrated in early-stage dementia, although successful explicit learning requires appropriate support at encoding and retrieval (Bäckman, 1992;Bird & Kinsella, 1996;Herlitz & Viitanen, 1991;Karlsson et al, 1989). Once information has been learnt, it may be retained over considerable periods (Clare, Wilson, Carter, Hodges, & Adams, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Given the promising evidence for subjective exit barrier effectiveness in reducing or eliminating exit-seeking 9 and results more equivocal for contingent reinforcement in dementia, 25,26 strategies matched not to health but to dementia models appear more promising. Combining informational sources also implies the value of targeting caregivers or cognitively intact others in lieu of wanderers, and/or, of circumventing ''wandering stakeholders'' altogether, focusing instead on modifying the dementia care environment.…”
Section: Framework Implicationsmentioning
confidence: 99%